EMPOWERING ENGLISH LANGUAGE LEARNING THROUGH SOCIAL LEARNING STRATEGIES IN VOCATIONAL SCHOOL - Eleonora Arista Dio Pramesti; Dias Andris Susanto (MARAS: Jurnal Penelitian Multidisiplin, 2023)
This study aims to investigate students' perceptions of Social Learning Strategy (SLS) in empowering various English as a Foreign Language (EFL) language skills in SMK N 6 Semarang. A descriptive qualitative method was used with a questionnaire survey to collect data from 35 students from SMK N 6 Semarang who completed the first nine items of the Strategy Inventory for Language Learning (SILL) questionnaire and a background characteristics survey. The study's findings indicate that how English is used in practice affects how well it is learned. The findings showed a connection between using social strategies and effectively learning English. The most commonly used social strategies are to mix Indonesian and English words if students do not know the English word or practice English with the English teacher and classmates.